2023
DOI: 10.1038/s41390-023-02499-0
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric sepsis diagnostic and prognostic biomarkers: pancreatic stone protein, copeptin, and apolipoprotein A-V

Abstract: Background We assessed serum concentrations of pancreatic stone protein (PSP), copeptin, and apolipoprotein A-V (APOA5) biomarkers for the diagnosis and prognosis of pediatric sepsis, a condition associated with high mortality. Methods This prospective study included 180 children admitted to the Pediatric Intensive Care Unit and 100 healthy controls at Menoufia University Hospital. Pediatric Risk of Mortality (PRISM), Pediatric Index of Mortality-2 (PIM2),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
0
4
0
1
Order By: Relevance
“…Аполипопротеин A-V − белок, который у человека кодируется геном APOA5, -копептин и PSP являются белками острой фазы, имеющими диагностическое значение при оценке тяжело больных детей с сепсисом и определении тяжести заболевания. PSP и копептин можно использовать для прогноза выживания при сепсисе [84].…”
Section: белок камней поджелудочной железыunclassified
“…Аполипопротеин A-V − белок, который у человека кодируется геном APOA5, -копептин и PSP являются белками острой фазы, имеющими диагностическое значение при оценке тяжело больных детей с сепсисом и определении тяжести заболевания. PSP и копептин можно использовать для прогноза выживания при сепсисе [84].…”
Section: белок камней поджелудочной железыunclassified
“…PSP together with apolipoprotein A-V and copeptin are acute-phase proteins that have a diagnostic value in the assessment of seriously ill children with sepsis. PSP and copeptin can be used to predict survival in sepsis [88].…”
Section: Pancreatic Stone Protein (Psp)mentioning
confidence: 99%
“…Searching for clinical studies of PSP and infection or sepsis in PubMed, we identified 1 prospective multicenter study, 29 20 prospective observational studies (Table 3 and 4), 2 meta-analyses, 30,31 2 literature reviews, 32,33 1 economic study, 34 2 technology study, 35,36 1 case report, 37 3 Covid-19 studies, [38][39][40] 1 book chapter, 41 2 point-of-view articles. 42,43 From the PubMed citations, we excluded 8 children studies, [44][45][46][47][48][49][50][51] 3 neonate studies, [52][53][54] 1 post-mortem study, 55 1 study in women for pregnancy-related disease, 56 1 PSP and diabetes study, 57 2 study protocols, 58,59 1 letter, 60 1 editorial, 61 4 comments, [62][63][64][65] and 1 published erratum. 66…”
Section: Pancreatic Stone Protein Clinical Studies For Infection and ...mentioning
confidence: 99%
“…35 Several classical ELISA kits with results obtained within 2 to 3 hours are used and commercialized in China. 46,48,83 In addition, the new Chinese AlphaLISA technology calibrated using an ELISA technic can also deliver results in 5 minutes. 36 PANCREATIC STONE PROTEIN ECONOMIC STUDY A 2021 independent US economic study showed that the use of PSP at a hypothetical price of 52 US$ could save the US healthcare system US$7 billion a year.…”
Section: Infection Hospitalized Patientmentioning
confidence: 99%